THE IMPORTANCE OF THE EUROPEAN SPACE AGENCY’S ACTIVITIES FOR THE SECURITY OF THE EUROPEAN UNION - BRYŁA, Jolanta (Przegląd Strategiczny, 2018)
The aim of this article is to show that the activities of the European Space Agency contribute significantly to the security of the European Union. What was required to develop space potential and to start using it for security purposes was the political and programmatic evolution of both organizations. The original objectives for which the European Space Agency was established were not related to security. Before the ESA became an organization with important implications for the security of the EU, it was an intergovernmental organization exclusively dedicated to the exploration and exploitation of space for peaceful purposes. The paper assumes that in order for this evolution to be possible, both the ESA and the EU had to find and/or develop common platforms and forms of possible cooperation. The paper identifies the most important reasons for and stages of this evolution, as expressed in program documentation. As this process is not yet complete, the remaining obstacles to the optimal use of the potential of both organizations to strengthen the security of the European Union are identified. The paper was created on the basis of the descriptive method, analysis of the content of documents and synthesis.